Correction to: do patients consider computer-adaptive measures more appropriate than static questionnaires? - Eva-Maria Gamper; Caroline Martini; Morten Aagaard Petersen; Irene Virgolini; Bernhard Holzner; Johannes M. Giesinger (SpringerOpen, 2019)
Following publication of the original article [1], the authors reported three of their given name have been erroneously tagged as their family names. The correct names are: give name Caroline family name Martini, give name Irene family name Virgolini, give name Bernhard family name Holzner.